Comparative study of intracranial access in thrombectomy using next generation 0.088 inch guide catheter technology. (26th May 2021) - Bageac, Devin V; Gershon, Blake S; Vargas, Jan; Mokin, Maxim; Ren, Zeguang; Chada, Deeksha; Turk, Aquilla S; Chaudry, M Imran; Turner, Raymond D; Fifi, Johanna T; Shigematsu, Tomoyoshi; De Leacy, Reade
Abstract : Background: Most conventional 0.088 inch guide catheters cannot safely navigate intracranial vasculature. The objective of this study is to evaluate the safety of stroke thrombectomy using a novel 0.088 inch guide catheter designed for intracranial navigation. Methods: This is a multicenter retrospective study, which included patients over 18 years old who underwent thrombectomy for anterior circulation large vessel occlusions. Technical outcomes for patients treated using the TracStar Large Distal Platform (TracStar LDP) or earlier generation TRX LDP were compared with a matched cohort of patients treated with other commonly used guide catheters. The primary outcome measure was device-related complications. Secondary outcome measures included guide catheter failure and time between groin puncture and clot engagement. Results: Each study arm included 45 patients. The TracStar group was non-inferior to the control group with regard to device-related complications (6.8% vs 8.9%), and the average time to clot engagement was 8.89 min shorter (14.29 vs 23.18 min; p=0.0017). There were no statistically significant differences with regard to other technical outcomes, including time to recanalization (modified Thrombolysis In Cerebral Infarction (mTICI) ≥2B). The TracStar was successfully advanced into the intracranial internal carotid artery in 33 cases (73.33%); in three cases (6.67%), it was swapped for an alternate catheter. Successful reperfusion (mTICI 2B-3) was achieved in 95.56% of cases. Ninety-day follow-up data were available for 86.67% of patients, among whom 46.15% had an modified Rankin Score of 0–2%, and 10.26% were deceased. Conclusions: Tracstar LDP is safe for use during stroke thrombectomy and was associated with decreased time to clot engagement. Intracranial access was regularly achieved.